Innovative COVID-19 point-of-care diagnostics suitable for tuberculosis diagnosis: a scoping review protocol - Yerlikaya, Seda; Holtgrewe, Lydia; Broger, Tobias; Isaacs, Chris; Nahid, Payam; Cattamanchi, Adithya; Denkinger, Claudia M. (BMJ open, 2023)
Introduction In 2014, the WHO published high-priority target product profiles (TPPs) for new tuberculosis (TB) diagnostics to align end-user needs with test targets and specifications; nevertheless, no TB test meets these targets to date. The COVID-19-driven momentum in the diagnostics world offers an opportunity to address the long-standing lack of innovation in the field of TB diagnostics. This scoping review aims to summarise point-of-care (POC) molecular and antigen tests for COVID-19 diagnosis that, when applied to TB, potentially meet WHO TPPs. This summary of currently available innovative diagnostic tools will guide the development of novel TB diagnostics toward the WHO-set targets. - Methods and analysis We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension Scoping Reviews recommendations. MEDLINE (via PubMed), bioRxiv, MedRxiv and other publicly available in vitro diagnostic test databases were searched on 23 November 2022. POC antigen or molecular tests developed for SARS-CoV-2 detection that meet the eligibility criteria will be included in the review. Developer description, test description, operation characteristics, pricing information, performance and commercialisation status of diagnostic tests identified will be extracted using a predefined standardised data extraction form. Two reviewers will independently perform the screening and data extraction. A narrative synthesis of the final data will be provided. - Ethics and dissemination No ethical approval is required because individual patient data will not be included. The findings will be published in open-access scientific journals.